The quality of insurance intermediary services: An analysis of conduct and performance in the German market of insurance intermediation - Martina Eckardt (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
Based on a sample of 946 German insurance intermediaries, the factors that affect the quality of the information services provided by them are studied using OLS-estimations. Applying a search theoretical approach, we analyze the impact of supply and demand side variables on service quality. Besides, the working of signaling devices (like reputation, advertising or certificates) to reduce asymmetric information with respect to the service quality of insurance intermediaries is examined. The results obtained support the main hypotheses derived from industrial organization theories as to the poor working of quality competition under incomplete and asymmetric information on the side of consumers. Thus, public policy should concentrate on increasing transparency about intermediaries' (in-)dependence from insurance companies and improve consumers' financial literacy to raise the overall quality of the information services provided by insurance intermediaries.
Keywords: D83; G22; L15; 330; Performance of Insurance Distribution Systems; Information Quality